2013
DOI: 10.1111/1471-0528.12262
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and ovulatory dysfunction

Abstract: Objective To explore the association between birthweight and ovulatory dysfunction in adulthood. Design Case–control study. Setting Northeast of Scotland University Hospital, hosting the regional fertility centre and maternity unit. Population A total of 18 846 mother–daughter record pairs from the Aberdeen Fertility Centre Data Set and the Aberdeen Maternity and Neonatal Databank (AMND). Cases were the daughters with ovulatory dysfunction attending the Aberdeen Fertility Centre between 1992 and 2007, Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Isso pode ser justificado por se tratar de uma das informações mais requeridas do recém-nascido, tanto pela sua família quanto pelos profissionais; para esses, o peso ao nascer é um dado fundamental, tendo em vista que algumas doenças que acometem os adultos estão relacionadas às alterações no crescimento e desenvolvimentos intrauterinos, a exemplo das doenças cardiovasculares, metabólicas e endócrinas na vida adulta (14) .…”
Section: Discussionunclassified
“…Isso pode ser justificado por se tratar de uma das informações mais requeridas do recém-nascido, tanto pela sua família quanto pelos profissionais; para esses, o peso ao nascer é um dado fundamental, tendo em vista que algumas doenças que acometem os adultos estão relacionadas às alterações no crescimento e desenvolvimentos intrauterinos, a exemplo das doenças cardiovasculares, metabólicas e endócrinas na vida adulta (14) .…”
Section: Discussionunclassified
“…Although SGA women in Brazil (Melo et al 2010) and those with LBW in Italy (Pandolfi et al 2008) and Turkey (Hizli et al 2012) present a higher risk for developing PCOS, these findings were not confirmed in individuals from the USA (Legro et al 2010), UK (Cresswell et al 1997, Michelmore et al 2001, Shayeb et al 2014, The Netherlands (Sadrzadeh et al 2003), Finland (Laitinen et al 2003), Spain (Ibáñ ez et al 2008) or Denmark (Mumm et al 2013). One study conducted in Australia analysed birth weight as a continuous variable and found that each 100 g increase in birth weight increased the risk of hyperandrogenism.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…The authors of that study also found that the subjects' thinness was related to PCOS symptoms and to IR (Davies et al 2012; Table 3). These apparent regional differences may result from the limitations of these studies, which include the use of varying definitions of PCOS (Cresswell et al 1997, Laitinen et al 2003, Sadrzadeh et al 2003, Ibáñ ez et al 2008, Hizli et al 2012, Mumm et al 2013, the inclusion of women using hormonal contraceptives (Ibáñ ez et al 2007, Davies et al 2012, Mumm et al 2013, the small numbers of participants (Ibáñez et al 2001, Pandolfi et al 2008, the use of self-reported birth data (Laitinen et al 2003, Sadrzadeh et al 2003, Legro et al 2010, Hizli et al 2012, the inclusion of women with immature HPG axes (Ibáñ ez et al 2001) and the absence of compensatory growth assessments (Cresswell et al 1997, Michelmore et al 2001, Laitinen et al 2003, Sadrzadeh et al 2003, Ibáñez et al 2008, Pandolfi et al 2008, Legro et al 2010, Melo et al 2010, Hizli et al 2012, Mumm et al 2013, Shayeb et al 2014. The use of birth weight classifications as an exposure factor across studies was perhaps the most important limitation, because not all of the studies adjusted the subjects' birth weight for GA. For that reason, some of the studies included preterm newborn infants.…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 2 more Smart Citations